2015
DOI: 10.1016/j.jcv.2015.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of a rapid point of care assay for early HIV antibody detection is enhanced by its ability to detect HIV gp41 IgM antibodies

Abstract: The INSTI HIV-1/HIV-2 Antibody Test is shown to detect anti-HIV-1 IgM antibodies in early HIV infection which enhances its utility in early HIV diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…A previous study characterized samples in commercially available seroconversion panels as containing detectable levels of either IgG-only, IgG and IgM, or IgM-only by depleting all IgM antibodies from the sample then testing with a reference ELISA and a POC antibody test ( Moshgabadi et al, 2015 ). Due to limited sample availability from the vendor, 15 of the 20 samples identified as being predominantly IgM (greater than 50% of total immunoglobulin content) were utilized in this study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study characterized samples in commercially available seroconversion panels as containing detectable levels of either IgG-only, IgG and IgM, or IgM-only by depleting all IgM antibodies from the sample then testing with a reference ELISA and a POC antibody test ( Moshgabadi et al, 2015 ). Due to limited sample availability from the vendor, 15 of the 20 samples identified as being predominantly IgM (greater than 50% of total immunoglobulin content) were utilized in this study.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study has demonstrated that POC tests using a Protein A-based detection system can detect samples with predominantly HIV-1 IgM reactivity ( Moshgabadi et al, 2015 ). The OraQuick ADVANCE ® Test also uses Protein A as the detection protein in the antibody-binding colloidal gold conjugate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such test is INSTI, a rapid HIV test approved by the Food and Drug Administration (FDA), which has shown a high sensitivity and specificity in diagnosing HIV infection in whole blood samples [ 8 ]. The INSTI rapid test has also been reported to perform well in identifying individuals with early HIV infection [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…A system using immunochromatographic membrane assay to detect the antigen of a fusion protein secreted by the respiratory syncytial virus (RSV) was also commercialized (Thuy Tien et al, 2018). Also, a variety of rapid tests for the diagnosis of HIV have been developed in the form of POC systems, such as the OraQuick Rapid HIV-1/2 antibody test and the fourth-generation HIV tests detecting both the antigen and antibodies, such as the AR-CHITECT HIV Ag/Ab combo and the Alere Determine HIV 1/2 Ag/Ab combo (Moshgabadi et al, 2015). Also, a variety of rapid tests for the diagnosis of HIV have been developed in the form of POC systems, such as the OraQuick Rapid HIV-1/2 antibody test and the fourth-generation HIV tests detecting both the antigen and antibodies, such as the AR-CHITECT HIV Ag/Ab combo and the Alere Determine HIV 1/2 Ag/Ab combo (Moshgabadi et al, 2015).…”
Section: Commercial Rapid Devices For Viral Detectionmentioning
confidence: 99%